Teknik Terapi Gestalt, Mengedepankan Komunikasi Interpersonal dalam Bimbingan dan Konseling Kelompok - Agung Tri Prasetia; Neviyarni Suhaili; Netrawati Netrawati (Institut Agama Islam Negeri Kerinci, Indonesia, 2022)
The main and most proposed paradigm in Gestalt theory is the integrity of the relationship between the individual and his environment, the good or considered individual who develops according to his development is the individual who understands how his environment is and how he is and what is the binding relationship between the personal self as an individual and his environment. The environment, which is closely related to culture, is the focus of the gestalt approach in explaining the environment for individuals. In this article, the discussion will focus on how interpersonal relationships motivated by culture become the